Análisis de las secuencias genéticas para la determinación de paternidad - Cando Manzano, Gabriela Alejandra (2023)
ABSTRACT: The objective of this research was to interpret the cytogenetic techniques for the diagnosis of trisomies, this type of aneuploidy is a health problem that affects all the general population because in many countries it cannot be detected in time due to the lack of equipment and specialized personnel, for this reason it has become necessary established strategic points on the prevalence of reported trisomies together with the cytogenetic techniques used for their identification, making comparisons through figures and tables for the systematic understanding of results through the investigation of descriptive type, collecting information from studies exposed in scientific databases of great international impact such as: Scielo, PubMed, Elsevier, Redalyc, Scopus, Google academic, as well as books and websites. The investigation consisted of a population of 130 and a sample of 41 bibliographic sources, applying selection criteria and data extraction such as the publication time of the integrated information between the years 2011 to 2021. The trisomies reported with the highest prevalence were trisomy 21,18 and 13, conventional and molecular cytogenetic techniques were identified, performing their interpretation and comparisons between advantages and disadvantages. The karyotype despite having. After many years of use, it continues to be the gold standard for the diagnosis of aneuploidies, while molecular techniques are faster in delivering results, they are not however, they are rarely used due to the restriction of analyzing the entire genome and with a much higher cost relative to karyotyping.